Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(x-1\right)^2=\left(x-1\right)^4\)
\(\Rightarrow\left(x-1\right)^2-\left(x-1\right)^4=0\)
\(\Rightarrow\left(x-1\right)^2.1-\left(x-1\right)^2.\left(x-1\right)^2=0\)
\(\Rightarrow\left(x-1\right)^2.\left[\left(x-1\right)^2-1\right]=0\)
\(\Rightarrow\orbr{\begin{cases}\left(x-1\right)^2=0\\\left(x-1\right)^2-1=0\end{cases}\Rightarrow\orbr{\begin{cases}x=1\\\left(x-1-1\right)\left(x-1+1\right)=0\end{cases}\Rightarrow}\orbr{\begin{cases}x=1\\x=2;x=0\end{cases}}}\)
Vậy: \(x\in\left\{1;2;0\right\}\)
\(\left(-2a^2b^3\right)^{10}+\left(3b^2.c^4\right)^{15}=0\)
=>\(\left(2a^2b^3\right)^{10}+\left(3b^2.c^4\right)^{15}=0\)
=>\(b^{30}.\left(2a^{20}+3c^{60}\right)=0\)
=> \(b^{30}=0\)hoặc \(2a^{20}+3c^{60}=0\)
=> \(b=0\)hoặc \(a^{20}=0\)hoặc \(c^{60}=0\)( vì \(a^{20}\ge0\)và \(c^{60}\ge0\))
=> b = 0 hoặc a =0 hoặc c = 0
b) ( 3x - 1 )2 = 25
( 3x - 1 )2 = 52 hoặc ( -5)2
tự làm
c) (-x + 5 )3 = -27
(-x + 5)3 = ( -3)3
-x + 5 = -3
-x = -8
x = 8
d) 4x + 4x+3 = 4160
4x . 1 + 4x . 43 = 4160
4x . ( 1 + 43 ) = 4160
4x . 65 = 4160
4x = 64
4x = 43
x = 3
e) dễ rồi
f) ( 2x- 1)6 = ( 2x-1 )8
( 2x - 1 )8 - ( 2x-1)6 =0
(2x-1)6 . [ (2x-1)2 - 1 ] = 0
\(\Rightarrow\orbr{\begin{cases}\left(2x-1\right)^6=0\\\left(2x-1\right)^2-1=0\end{cases}}\)
tự làm
a) ( 2x + 5 )2 = 81
\(\orbr{\begin{cases}\left(2x+5\right)^2=9^2\\\left(2x+5\right)^2=\left(-9\right)^2\end{cases}}\)
\(\orbr{\begin{cases}2x+5=9\\2x+5=-9\end{cases}}\)
\(\orbr{\begin{cases}2x=4\\2x=-14\end{cases}}\)
\(\orbr{\begin{cases}x=2\\x=-7\end{cases}}\)
\(5^{45}=5.\left(5^2\right)^{22}=5.25^{22}\)
\(3^{73}=3^4.\left(3^3\right)^{23}=81.27^{23}\)
\(\Rightarrow5^{45}< 3^{73}\)
\(2^{83}=2^2.\left(2^3\right)^{27}=4.8^{27}\)
\(3^{57}=3^3.\left(3^2\right)^{27}=27.9^{27}\)
\(\Rightarrow2^{83}< 3^{57}\)
\(\Leftrightarrow3.\left(7x^2+1\right)=4.\left(8x^2-2\right)\)
\(\Leftrightarrow21x^2+3=32x^2-8\)
\(\Leftrightarrow21x^2+3-32x^2+8=0\)
\(\Leftrightarrow-11x^2+11=0\)
\(\Leftrightarrow-11\left(x^2-1\right)=0\)
\(\Leftrightarrow x^2-1=0\)
\(\Leftrightarrow x^2=1\)
\(\Leftrightarrow x=1\)
#quankun^^
\(\left(7x^2+1\right):4=\left(8x^2-2\right):3\)
\(\frac{7x^2+1}{4}=\frac{8x^2-2}{3}\)
\(\left(7x^2+1\right).3=\left(8x^2-2\right).4\)
\(21x^2+3=32x^2-2\)
\(21x^2-32x^2=-2-3\)
\(-11x^2=-5\)
\(x^2=\frac{5}{11}\)
\(x^2=\sqrt{\frac{5}{11}}=\frac{\sqrt{55}}{11}\)